Trwamy . gazeta strajkowa, no. 11, 1981 - [ed. Jarosław Szczepański] ([NSZZ "Solidarność"], 1981)
Creation and circulation: After introduction of the Martial Law publication suspended. Republished underground in 1984-1985 as the press organ of RKW NSZZ "Solidarność"